"أهمية الصلابة النسبية في حساب جدار القص بفتحة المقاوم للزلازل" - شرف, طلال (Latakia University Journal -Engineering Sciences Series, 2018)
The relative stiffness of the shear diaphragm is determined by with hole of the calculation method as an open shear diaphragm or as shear diaphragm to resist the side loads caused by earthquakes and to maintain the stability of the building, given its importance, the computational relations required for the relative stiffness of the shear diaphragms were extracted, and strengthen weak structural elements such as beams between the wings of the shear diaphragm or columns and beams in the wholesale frame, To increase its resistance to side loads caused by seismic intensity in simplified ways in accordance with the terms and conditions of the code in our region. Mathematical relationships have been developed and reinforced by the results of the experiments [8], which are included in the calculation of variables for the self-vibration coefficient of construction (), the role of self-vibration (), and Flexibility factor (S), [relationships (14)], for shear diaphragm elements with equal or different openings, to determine the magnitude of side forces resulting from earthquakes (on the level of floor tiles and at full height construction. The calculate the reinforcing steel bars area has been proposed according to experimental results and theoretical research in recent years, And the calculation of ray sections in accordance with the theory of Gvazdeyev at the stage of collapse , A verification application has been applied. The comparison between the behavior of the beams association clips fixed and variable inertia Association beams for the shear diaphragms with openings to apply the proposed theoretical relationships and experimental research and compare the results and determine their resistance to seismic loads and verified. تحدد قيمة الصلادة النسبية لجدار القص بفتحة طريقة حسابه كجدار قص بفتحة أو كجدار قص مصمت لمقاومة الحمولات الجانبية الناتجة عن الزلازل والحفاظ على استقرار البناء، ونظرا "لأهميته، فقد تم استخراج العلاقات الحسابية اللازمة للصلابة النسبية لجدران القص، وتقوية العناصر الإنشائية الضعيفة كالجوائز بين أجنحة جدار القص أو الاعمدة والجوائز في الجملة الإطارية (الكمرة)، لزيادة مقاومتها للأحمال الجانبية الناتجة عن الشدة الزلزالية بطرق مبسطة بما يتوافق مع الشروط والمواصفات للكود في منطقتنا. تم استنباط علاقات حسابية مدعمة بالبحث التجريبي [8] والتي تدخل في حساب المتغيرات لمعامل الاهتزاز الذاتي للبناء () ودور الاهتزاز الذاتي ()]العلاقة (14)[والمطاوعة (S)لعناصر جدار القص بفتحات متساوية (أو مختلفة) لتحديد شدة القوى الجانبية الناتجة عن الزلازل (على منسوب البلاطات الطابقية وعلى ارتفاع كامل البناء. تم اقتراح توضع التسليح للجوائز بما يوافق النتائج التجريبية والبحوث النظرية في الأعوام الأخيرة، وحساب مقاطع الجائز، بالنظرية الحدية في مرحلة الانهيار (المرحلة الثالثة:(,وتم إجراء تطبيق حسابي للتحقق. تم إجراء مقارنة بين تشوه الجوائز الرابطة بمقاطع ثابتة وجوائز رابطة متغيرة العطالة لجدران القص بفتحة بتطبيق العلاقات النظرية المقترحة والبحوث التجريبية ومقارنة النتائج وتحديد مقاومتها للأحمال الزلزالية والتحقق من النتائج.